2008
DOI: 10.1021/ja802404g
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Activation of Enzymatic Catalysis

Abstract: Microwave irradiation can be used to regulate biocatalysis. Herein, the utilization of hyperthermophilic enzymes in a microwave reactor is reported. While these enzymes are inactive at low temperatures, they can be activated with microwave irradiation. To the best of our knowledge, this is the first illustration of a specific microwave effect in enzymatic catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 24 publications
1
65
0
2
Order By: Relevance
“…As an example, these effects are used in biocatalysis discipline (Réjasse et al, 2004;2006;Yadav & Borkar, 2009;Souza et al, 2009), DNA hybridization (Edwards, Young, & Deiters, 2009) and the studies that evaluate enzyme stability with the use of microwave irradiation (Rejasse et al, 2007;Young et al, 2008;Izquierdo et al, 2007;Porcelli et al, 1997;La Cara et al, 1999). Recently, Laurence et al (2000), H. Bohr and J. Bohr (2000), Pomerai et al (2003) reported unfolding or structural changes in proteins with microwave irradiations and suggested the inclusion of www.ccsenet.org/ijc…”
Section: Applications In Proteomicsmentioning
confidence: 99%
“…As an example, these effects are used in biocatalysis discipline (Réjasse et al, 2004;2006;Yadav & Borkar, 2009;Souza et al, 2009), DNA hybridization (Edwards, Young, & Deiters, 2009) and the studies that evaluate enzyme stability with the use of microwave irradiation (Rejasse et al, 2007;Young et al, 2008;Izquierdo et al, 2007;Porcelli et al, 1997;La Cara et al, 1999). Recently, Laurence et al (2000), H. Bohr and J. Bohr (2000), Pomerai et al (2003) reported unfolding or structural changes in proteins with microwave irradiations and suggested the inclusion of www.ccsenet.org/ijc…”
Section: Applications In Proteomicsmentioning
confidence: 99%
“…Microwave irradiation have been used in various processes, such as chemical reaction [19,20], material synthesis [21], nanotechnology [22] and biochemical processes [23,24]. It has been reported that microwave irradiation could raise the yield and reduced the reaction time in the synthesis of carbonates from CO 2 and epoxide [25], NaHCO 3 and olefins [26], CO and diols [27], and polycarbonates from open-ring polymerization of trimethylene carbonate [28].…”
Section: Introductionmentioning
confidence: 99%
“…Microwave irradiation results in an instantaneous localized superheating which is achieved due to dipole rotation or ionic conduction. Microwave irradiation has been applied to the synthesis of several natural products as well as peptides, peptoids and carbohydrates [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%